2008
DOI: 10.1007/s11262-008-0257-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of a novel group A lamb rotavirus isolated in Zaragoza, Spain

Abstract: An ovine rotavirus (OVR) strain, 762, was isolated from a 30-day-old lamb affected with severe gastroenteritis, in Zaragoza, Spain, and the VP4, VP7, VP6, NSP4, and NSP5/NSP6 genes were subsequently characterized molecularly. Strain OVR762 was classified as a P[14] rotavirus, as the VP4 and VP8* trypsin-cleavage product of the VP4 protein revealed the highest amino acid (aa) identity (94% and 97%, respectively) with that of the P11[14] human rotavirus (HRV) strain PA169, isolated in Italy. Analysis of the VP7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…Several human G6P [14] strains (MG6, MG6.01, aG6.01, and ASG6.02) were isolated in south and central Australia between 1993 and 1997 (9,11,36), and one G6P [14] isolate (Hun5) was identified in Hungary in 1997 (4). The VP4 proteins of the human G6P [14] strains are more closely related to those of strains isolated from sheep (OVR762), goats (Cap455), cattle (Sun9, RUBV81), and guanacos (Arg/Chubut/99), all even-toed ungulates belonging to representative species of the order Artiodactyla, than to those from rabbits (ALA, C-11, BAP-2, and 30/96) (8,15,38).…”
Section: ) These Analyses Revealed An Overall Consensus Genomic mentioning
confidence: 92%
See 3 more Smart Citations
“…Several human G6P [14] strains (MG6, MG6.01, aG6.01, and ASG6.02) were isolated in south and central Australia between 1993 and 1997 (9,11,36), and one G6P [14] isolate (Hun5) was identified in Hungary in 1997 (4). The VP4 proteins of the human G6P [14] strains are more closely related to those of strains isolated from sheep (OVR762), goats (Cap455), cattle (Sun9, RUBV81), and guanacos (Arg/Chubut/99), all even-toed ungulates belonging to representative species of the order Artiodactyla, than to those from rabbits (ALA, C-11, BAP-2, and 30/96) (8,15,38).…”
Section: ) These Analyses Revealed An Overall Consensus Genomic mentioning
confidence: 92%
“…G1, G3, G4, and G9 (associated with P [8]) and G2 (associated with P [4]) are the epidemiologically most important human rotavirus genotypes worldwide (47). G12 might be the next important emerging strain, as it has been identified in sporadic cases and outbreaks in countries around the world (3, [6] in Africa or, more specifically, G8P [6] in Malawi and G5P [8] in Brazil, are regionally prevalent (1,10,29,47).…”
Section: ) These Analyses Revealed An Overall Consensus Genomic mentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic analysis of 04-97s379 showed that it is divergent from other reported human isolates that carry the same G and P antigen types (e.g., isolates from Finland, Italy, Australia, Hungary, or Egypt) (6-9) and also that it differs from animal G8P[14] strains identified in Japan, India (bovine), Spain (ovine), or Argentina (guanaco) (7,(10)(11)(12). Although the Taiwanese human G8P[14] strain was found to be somewhat similar to the Indian bovine G8P[14] strains when comparing the respective VP7 and VP6 genes, the VP4 and NSP4 genes were clearly divergent (11).…”
Section: Communicated By Takaji Wakita (Accepted July 3 2012)mentioning
confidence: 99%